Nguyen Thu Ha
2 tháng 1 2017 lúc 8:47

 Ta có 1/a + 1/b + 1/c = (bc + ca + ab)/abc = ab + bc + ca ( vì abc =1)=> a + b + c = ab + bc + ca <=> a + b + c - ab - bc - ca = 0 <=> a + b + c - ab - bc - ac + abc - 1 = 0 <=> (a - ab) + (b - 1) + (c - bc) + (abc - ac) = 0 <=> -a(b - 1) + (b - 1) - c(b - 1) + ac(b - 1) = 0 <=> (b - 1)(-a + 1 -c + ac) = 0 <=> (b - 1)[ (-a + 1) + (ac - c) ] = 0 <=> (b - 1)[ -(a - 1) + c(a - 1) ] = 0 <=> (a - 1)(b - 1)(c - 1) = 0 <=> a - 1 = 0 hoặc b - 1 = 0 hoặc c - 1 = 0 <=> a = 1 hoặc b = 1 hoặc c = 1 

Bình luận (0)
Vũ Tuấn Anh
2 tháng 1 2017 lúc 8:59

A=0

B=0

C=1

k mình nhé!Đúng 100%!

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN